PSYCHOLOGICAL FACTORS OF STYLISTIC FEATURES MANIFESTATION IN PEDAGOGICAL COMMUNICATION - I V Arendachuk (Peoples' Friendship University of Russia (RUDN University), 2016)
The article deals with the contemporary theoretical approaches to defining such concepts as "pedagogical communication" and "the style of pedagogical communication", the substantial features of pedagogical communication in the system of the teachers' attitude to their students, their professional work and themselves are revealed. The results of the empirical research conducted on a sample of Saratov secondary school teachers ( n = 67; average age of 42 years old; average length of service of 18 years), intended to identify the relationships between the style of pedagogical communication and its psychological factors (personal and practical) are demonstrated in the article. We used the methods of determining the style of interpersonal interaction (S.V. Maksimov, Yu.A. Lobeiko), diagnostics of dominant emotional modality in teachers (L.A. Rabinovich in T.G. Syritso's modification), satisfaction evaluation of the profession of a teacher and identification of crisis factors and factors of overcoming the professional crisis of teachers (O.M. Chorosova, R.E. Gerasimova); the method of "psychological portrait of a teacher" (Z.V. Rezapkina, G.V. Rezapkina). The article demonstrates that the more constructive the style of pedagogical communication is, the larger number of psychological factors it has, and the system of these factors is dominated by the factors that characterize the individual features of the teacher's personality.